Scientific Literacy and Climate Change Perceptions among Junior High School Students in Medan: Insights from the PISA Framework - Widia Ningsih; Aristo Hardinata; Rahmi Nazliah; Muhammad Azhari (Jurnal Penelitian Pendidikan IPA, 2026)
Climate change is a global issue that requires scientific understanding and pro-environmental awareness, making scientific literacy and student perceptions important factors. This study analyzes the scientific literacy and perceptions of junior high school students in Medan City regarding climate change and the relationship between the two based on the PISA 2025 framework. The research design uses a quantitative descriptive approach with a correlational method, involving 130 students from five junior high schools selected through purposive sampling. The instruments included perception questionnaires (cognitive, affective, and conative dimensions) and scientific literacy tests (explaining phenomena, designing investigations, and evaluating information). The results showed that students' conceptual understanding and pro-environmental behavior were high, but their motivation and concern were moderate. Scientific literacy was strongest in evaluating and using information, while the ability to explain phenomena and design investigations still needed improvement. Correlation analysis showed a weak and non-significant positive relationship between perception and scientific literacy (r = 0.113; p = 0.201), indicating that perception alone was not a major factor in achieving scientific literacy. These findings emphasize the need for inquiry-based science learning, projects, problem-based learning, and the use of local contexts, which integrate the strengthening of knowledge, attitudes, and real practices. These strategies are expected to improve scientific literacy as a whole and shape students as agents of change in facing the challenges of climate change.